2011
DOI: 10.1590/s0103-21002011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento dos diagnósticos de enfermagem em uma unidade de pneumologia

Abstract: RESUMOObjetivos: Identificar os diagnósticos de enfermagem mais frequentes, segundo a taxonomia II da NANDA -I; as características definidoras, fatores relacionados e de risco que deram suporte para elaboração dos mesmos, em pacientes com distúrbios respiratórios. Métodos: Estudo transversal, realizado em um hospital universitário da cidade de São Paulo. Os diagnósticos de enfermagem foram elaborados pela pesquisadora e submetido à validação consensual de três especialistas. Os resultados foram descritos basea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
0
5
0
4
Order By: Relevance
“…In the domain Elimination and exchange, the presence of the diagnostic label Impaired gas exchange was identified, which was related to the presence of secretions in the airways and hindered proper gas exchanges to the use of ventilatory support and complications such as pulmonary edema and respiratory failure. This diagnosis was also identified in another study with patients hospitalized in ICUs (16)(17) with respiratory disorders. The DCs evidenced in these studies include shortness of breath on mild exertion and altered arterial blood gas (70%); also, during the physical examination abnormal breathing was observed by alteredrate or depth, and tachycardia.…”
Section: Discussionmentioning
confidence: 61%
“…In the domain Elimination and exchange, the presence of the diagnostic label Impaired gas exchange was identified, which was related to the presence of secretions in the airways and hindered proper gas exchanges to the use of ventilatory support and complications such as pulmonary edema and respiratory failure. This diagnosis was also identified in another study with patients hospitalized in ICUs (16)(17) with respiratory disorders. The DCs evidenced in these studies include shortness of breath on mild exertion and altered arterial blood gas (70%); also, during the physical examination abnormal breathing was observed by alteredrate or depth, and tachycardia.…”
Section: Discussionmentioning
confidence: 61%
“…19 It's known that the passive smoker also has a potential risk for chronic diseases, such as the chronic lung disease which potentiates the heart diseases. 20 This way, the professionals should perform health education practices which mobilize users for participation in programs for fighting smoking, 21 thus minimizing the risk factors for chronic heart diseases. The nursing professionals may act proposing measures for controlling tobacco use among cardiac patients, explaining and demonstrating that abstinence leads to control of hypertension and/or heart diseases.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4] Thus, the pain, if not properly treated, is a potent stressor, triggering important physical or emotional responses, contributing to the worsening of the patient's prognosis. [5][6] In addition to this, it is often the great prevalence of patients undergoing major surgeries that relate the intensity of pain ranging from moderate to intense. The example of pain expressed post-myocardial re-vascularization by sternotomy, a study conducted with patients who have been subjected to this type of surgery, showed that on a numerical scale from 0 (zero) to ten (ten), the intensity of pain reported ranged between 7 (seven) and 10 (ten).…”
mentioning
confidence: 99%
“…However, there are reports of consistent underestimation in the diagnosis and evaluation of pain, especially in intensive care environments, in which the difficulty or impossibility of the patient in expressing consciously the pain, make them even more difficult. [5][6] In a study conducted in an intensive care unit, where 39 coronary patients were evaluated, it was conclusive that the pain was predominant and there was no correlation between pain and the presence of physiological changes evaluated, being the most frequent tachypnea (45.0%) and increase in blood pressure(24.5%).…”
mentioning
confidence: 99%